2011 IEEE 61st Electronic Components and Technology Conference (ECTC) 2011
DOI: 10.1109/ectc.2011.5898608
|View full text |Cite
|
Sign up to set email alerts
|

TSV based silicon interposer technology for wafer level fabrication of 3D SiP modules

Abstract: Silicon interposers with through silicon vias (TSVs) have become important key components of 3D architectures. They are used as intermediate carrier and wiring device for IC components like logics, memories and sensors. Due to custom specific front and back side wiring interposers enable to adapt the fine pitch IO terminals of the mounted ICs to the IO geometries of the package level. High density copper filled TSVs with high aspect ratio as well as high density multi layer wiring using electro plated copper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…3) Hybrid Paradigm Using 2.5D On-chip Voltage Regulators with Interposer: Fig.4(c) gives a cross-section view of a hybrid power delivery system paradigm utilizing a 2.5D stacking silicon interposer, which is commonly used to extend the communication bandwidth of many-core processors [34]. The on-chip voltage regulators and the target processor chip are both mounted on the silicon interposer with micro-bumps.…”
Section: B Modeling Of Different Power Delivery System Paradigmsmentioning
confidence: 99%
“…3) Hybrid Paradigm Using 2.5D On-chip Voltage Regulators with Interposer: Fig.4(c) gives a cross-section view of a hybrid power delivery system paradigm utilizing a 2.5D stacking silicon interposer, which is commonly used to extend the communication bandwidth of many-core processors [34]. The on-chip voltage regulators and the target processor chip are both mounted on the silicon interposer with micro-bumps.…”
Section: B Modeling Of Different Power Delivery System Paradigmsmentioning
confidence: 99%
“…The most widely so called Bosch Process is used to fabricate vias with vertical sidewalls [1]. For Applications like interposers for processors, there exists the demand to produce TSVs with high aspect ratios [2] due to the high connection density and the necessary minimal thickness of the module caused by the assembly process. Subsequent processing of these etched holes in form of liner, barrier and seed layer deposition can become challenging and therefore increases costs.…”
Section: Plasma Etching Of Tapered Via Structuresmentioning
confidence: 99%
“…Zoschke et al reported their whole process for wafer level fabrication of 2.5D SiP modules , where the silicon interposer in the flip clip was bonded to a pin grid array (PGA) organic substrate [7]. While for the whole 2.5D IC integration process using ball grid array (BGA) organic substrate , the Cu/low-k silicon interconnected with silicon interposer through I lCPBs will undergo three times of lead free reflow process : a. the first level assembly between Cu/low-k silicon die and silicon interposer wafer , b. the second level component assembly between the silicon interposer and organic substrate , c. the third level assembly between the component and printed circuit board (PCB).…”
Section: Introductionmentioning
confidence: 99%